The - Rutledge, David B. (Cambridge University Press, 1999)
This innovative book provides a stimulating introduction to analog electronics by analyzing the design and construction of a radio transceiver. The author provides essential theoretical background at each step, along with carefully designed laboratory and homework exercises. This structured approach ensures a good grasp of basic electronics as well as an excellent foundation in wireless communications systems. The author begins with a thorough description of basic electronic components and simple circuits. He then describes the key elements of radio electronics, including filters, amplifiers, oscillators, mixers, and antennas. In the laboratory exercises, he leads the reader through the design, construction, and testing of a popular radio transceiver (the NorCal 40A), thereby illustrating and reinforcing the theoretical material. A diskette containing the widely known circuit simulation software, Puff, is included in the book